PEMODELAN PRODUKSI BIOETANOL OLEH SACCHAROMYCES CEREVISIAE DENGAN SUBSTRAT GLUKOSA - Muhammad Syach, Adam
Petroleum resource depletion demands the development of mass-producible alternative energy sources. Bioethanol is one of the easiest examples of renewable energy to implement. Bioethanol is produced by fermentation using the yeast Saccharomyces cerevisiae.This study will determine the effect of different concentrations of glucose (10, 20, and 30 g/L) on yielding biotanol. affect the production of biotanol .This study also develops a fermentation model of the effect of different conditions of fermentation temperature (30, 33, 35, 38, and 42 oC) on the specific growth rate and determines the activation energy of the fermentation process using Arrhenius models. The research method is divided into several stages, namely: preparation, simple research, analysis of results, and modeling. Preparation in the form of yeast subculture on agar slanted, medium preparation, yeast activation on ammonium-glucose medium, making glucose standard curve, and making cell standard curve. Simple research in the form of fermentation in batch with variations in the concentration of glucose substrate. Analysis of the results in the form of interpretation of the data obtained during a simple study consisting of glucose concentration, ammonia concentration and cell concentration. The modeling consists of modeling batch fermentation with temperature variations using the MATLAB application with the ode45 function and the Arrhenius model to determine the activation energy value. According to the study's findings, the optimal starting glucose content was 30 g/L, with a bioethanol yield of 0.44 grams of ethanol/gram of glucose. The fermentation optimal temperature in the model is 35 oC, with a bioethanol output of 0.4 grams ethanol/gram of glucose, a specific growth rate (?) value of 0.58 h-1, and an activation energy value of 31.4 kJ/mol.